2006
DOI: 10.1530/eje.1.02093
|View full text |Cite
|
Sign up to set email alerts
|

Vascular and renal function in experimental thyroid disorders

Abstract: This review focuses on the effects of thyroid hormones in vascular and renal systems. Special emphasis is given to the mechanisms by which thyroid hormones affect the regulation of body fluids, vascular resistance and, ultimately, blood pressure. Vascular function is markedly affected by thyroid hormones that produce changes in vascular reactivity and endothelial function in hyper-and hypothyroidism. The hypothyroid state is accompanied by a marked decrease in sensitivity to vasoconstrictors, especially to sym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
196
1
12

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 242 publications
(216 citation statements)
references
References 177 publications
7
196
1
12
Order By: Relevance
“…Nongenomic actions target membrane ion channels and endothelial nitric oxide synthase, which serves to decrease SVR. 29,30 Relaxation of VSM leads to decreased arterial resistance and pressure, which thereby increases cardiac output. Increased endothelial nitric oxide production may result, in part, from the T 3 -mediated effects of TR on the protein kinase akt pathway either via nongenomic or genomic mechanisms.…”
Section: Effects Of Thyroid Hormone On Cardiovascular Hemodynamicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nongenomic actions target membrane ion channels and endothelial nitric oxide synthase, which serves to decrease SVR. 29,30 Relaxation of VSM leads to decreased arterial resistance and pressure, which thereby increases cardiac output. Increased endothelial nitric oxide production may result, in part, from the T 3 -mediated effects of TR on the protein kinase akt pathway either via nongenomic or genomic mechanisms.…”
Section: Effects Of Thyroid Hormone On Cardiovascular Hemodynamicsmentioning
confidence: 99%
“…The observation that hyperthyroidism is associated with increased vascularity suggests that T 3 may increase capillary density via increased angiogenesis. 29 Adrenomedullin, a polypeptide of 52 amino acids, is a potent vasodilator transcriptionally regulated by thyroid hormone, and serum levels are increased in thyrotoxicosis. 33 Interestingly, however, Diekman and colleagues 34 demonstrated that although SVR is decreased and adrenomedullin is increased in thyrotoxicosis, restoration of euthyroidism normalized SVR but was not correlated with plasma adrenomedullin levels.…”
Section: Effects Of Thyroid Hormone On Cardiovascular Hemodynamicsmentioning
confidence: 99%
“…There were many methods to produce an animal model of kidney yin deficiency in TCM science, and thyroxine combined with reserpine is the most commonly used approach [9]. Large doses of thyroxine could lead to hyperthyroidism coupled with the symptoms of weight loss, increased kidney weight, and elevated blood pressure and heart rate [24], which were similar to the typical symptoms of kidney yin deficiency. We observed that the rats in kidney yin deficiency model group had clinical symptoms of kidney yin deficiency after thyroxine and reserpine administration for 10 days.…”
Section: Urinary Metabolic Profiling Study Of Rg Treating Kidney Yin mentioning
confidence: 99%
“…After the raw RG was prepared for the processed one, the increased 5-HMF was the most significantly changed component. Kidney yin deficiency is usually accompanied by oxidative stress in the body, in which large doses of thyroxine could lead to a hypermetabolic condition with the presence of lipid peroxide and increased free radical levels [24][25][26]. Interestingly, 5-HMF has a structural reducing property that has an antioxidant effect by means of suppressing the activity of caspase-3 and decreasing NO [27][28][29].…”
Section: Relationship Between Quality Marker Components and The Treatmentioning
confidence: 99%
“…Central administration of CRH elevates blood pressure and heart rate, whereas peripheral administration of CRH results in vasodilatation and decreased blood pressure (Parkes et al, 2001). Thyroid hormones as the end-effectors of the HPT axis also have a pronounced effect on the cardiovascular system, for example, hyperthyroidism results in increased cardiac output, heart rate, pulse and blood pressure, and decreased vascular peripheral resistance (Vargas et al, 2006).…”
Section: Introductionmentioning
confidence: 99%